2021
DOI: 10.1259/bjro.20210034
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced mammography: what the radiologist needs to know

Abstract: Contrast-enhanced mammography (CEM) is a combination of standard mammography and iodinated contrast material administration. During the last decade, CEM has found its place in breast imaging protocols: after i.v. administration of iodinated contrast material, low-energy and high-energy images are retrieved in one acquisition using a dual-energy technique, and a recombined image is constructed enabling visualisation of areas of contrast uptake. The increased incorporation of CEM into everyday clinical practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 76 publications
0
19
0
1
Order By: Relevance
“…Since the early days of CEM implementation, its use in the evaluation of abnormalities detected at screening mammography has been one of the most reported applications [ 14 , 15 ]. Albeit with some caveats related to the contrast uptake of benign lesions [ 14 , 15 ] and to equivocal enhancement conspicuity associated with calcifications clusters [ 29 31 ], retrospective studies have highlighted the potential of CEM to increase the PPV of the work-up process without compromising cancer detection [ 31 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the early days of CEM implementation, its use in the evaluation of abnormalities detected at screening mammography has been one of the most reported applications [ 14 , 15 ]. Albeit with some caveats related to the contrast uptake of benign lesions [ 14 , 15 ] and to equivocal enhancement conspicuity associated with calcifications clusters [ 29 31 ], retrospective studies have highlighted the potential of CEM to increase the PPV of the work-up process without compromising cancer detection [ 31 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the early days of CEM implementation, its use in the evaluation of abnormalities detected at screening mammography has been one of the most reported applications [ 14 , 15 ]. Albeit with some caveats related to the contrast uptake of benign lesions [ 14 , 15 ] and to equivocal enhancement conspicuity associated with calcifications clusters [ 29 31 ], retrospective studies have highlighted the potential of CEM to increase the PPV of the work-up process without compromising cancer detection [ 31 35 ]. We investigated this issue in a prospective setting, assessing the diagnostic gain granted by contrast-enhanced (rCEM) images, since low-energy CEM images—equivalent to standard mammograms [ 26 , 27 ]—are also available in the SA process used as a comparator.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, MRI is very important in the diagnosis of breast cancer. MRI has many advantages, including that it is non-invasive, does not involve exposure to radiation, has high resolution, and can intuitively display the morphological and functional information of breast cancer, which will increase the accuracy of breast cancer diagnosis (14)(15)(16). Numerous studies (17)(18)(19)(20) have found that imaging groups can be used to predict the diagnosis, type, and lymph node metastasis of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Since its introduction in 2011, the use of contrast-enhanced mammography (CEM) has been steadily increasing in both research and clinical settings [7][8][9][10]. A CEM examination, in which an iodinated contrast agent is administered followed by the acquisition of a dual-energy mammography, uses the same physiological contrast enhancement principle as breast MRI [8].…”
Section: Introductionmentioning
confidence: 99%